PBDEs in environmental samples: Sampling and analysis - KROL, Sylwia; ZABIEGALA, Bozena; NAMIESNIK, Jacek (Talanta (Oxford), 2012)
► The review describes commonly used analytical procedures for determining PBDE in environmental samples. ► Information on the subsequent stages of analytical procedure (e.g. sample collection, extraction, clean up, etc.) is presented. ► The special attention is paid to the newly developed and promising microextraction techniques. ► Authors describe the limitations that may occur during the analysis of highly brominated congeners (e.g. BDE209). The paper reviews the subject literature concerning analytical procedures routinely sed for monitoring polybrominated diphenyl ethers (PBDE) in environmental samples. It describes and summarizes subsequent stages of analytical procedure including sample collection and preparation, extraction, clean-up and final determination. Different approaches with their advantages and limitations are presented. Special attention is drawn to the newly developed, promising extraction techniques, especially: liquid–liquid-microextraction (LLME) with its modifications, cloud point extraction (CPE) and hollow fiber microextraction. The review compares available detection techniques taking into account their usefulness for determining different PBDEs in complex matrix as well as discussing possible limitations that may occur during the analysis. The quality assurance and quality control aspect of analytical procedure is described. Finally special attention is paid to the determination of highly brominated PBDE compounds (e.g. BDE209), which requires implementation of different analytical approach.